PENGARUH KINERJA KEUANGAN TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (StudiEmpirisPada Sektor Industri Barang Konsumsi Yang Terdaftar Di Bursa Efek Indonesia) - admin, SUMI VIRRIYANTI B11111026 (Jurnal Manajemen Update, 2016)
This study aims to analyze how the influence of the financial performance of companies to Disclosure of Corporate Social Responsibility. Financial performance using five variables Return on Assets , Debt to Equity Ratio , Current Ratio , company size , and Operating Cash Flow. This study uses empirical data from the Consumer Goods Industry Sector listed on the Indonesia Stock Exchange (IDX) for the period 2011-2014 . The population amounted to 41 companies using sample selection by purposive sampling technique acquired 20 companies which will be used as a sample. Measurement of corporate social responsibility is based on thecategory of the Global Reporting Index (GRI) version 3.0 is seen in the company's annual financial report.                Results of research conducted can be concluded that the financial performance in proxied by the Current Ratio has significant influence on Corporate Social Responsibility. Other variables are Return On Assets, Debt to Equity Ratio , company size , and Operating Cash Flow do not have a significant effect on Corporate Social Responsibility.   Keywords : Financial Performance , Return on Assets , Debt to Equity Ratio ,Current Ratio , Company Size , Operating Cash Flow , Corporate Social Responsibility.